2021
DOI: 10.1051/e3sconf/202131901017
|View full text |Cite
|
Sign up to set email alerts
|

Unintentional Accidents among Children: Associated Factors with moderate /severe forms

Abstract: Unintentional accidents are very common in children and are the main reason for consultation and hospitalization in paediatric surgery. Aim: To determine the factors associated with unintentional accidents resulting in hospitalization. Material and methods: This is a cross sectional study carried out in the Paediatric Surgical Emergency Department of the Children's Hospital of Rabat over a period of 4 years. We processed 1205 children's files; the data was collected and analysed by Jamovi. Results: for the 545… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…11 We also found out the percentage of injuries that had taken place during the weekends (28.1 %) in relation to weekdays (71.8 %) which is in accordant with an analysis study done in Morocco. 12 In opposition to this a study conducted in Karachi mentions weekends bearing more reported cases. 13 Domestic injuries (69.9%) were observed to be in majority, which is similar to a compelling study conducted in Nepal and Saudi Arabia.…”
Section: Discussionmentioning
confidence: 91%
“…11 We also found out the percentage of injuries that had taken place during the weekends (28.1 %) in relation to weekdays (71.8 %) which is in accordant with an analysis study done in Morocco. 12 In opposition to this a study conducted in Karachi mentions weekends bearing more reported cases. 13 Domestic injuries (69.9%) were observed to be in majority, which is similar to a compelling study conducted in Nepal and Saudi Arabia.…”
Section: Discussionmentioning
confidence: 91%